2010
DOI: 10.1097/hjh.0b013e328336ade3
|View full text |Cite
|
Sign up to set email alerts
|

Cilnidipine suppresses podocyte injury and proteinuria in metabolic syndrome rats: possible involvement of N-type calcium channel in podocyte

Abstract: Objectives-Clinical studies have indicated the beneficial effect of an L/N-type calcium channel blocker (CCB), cilnidipine, on the progression of proteinuria in hypertensive patients compared with an L-type CCB, amlodipine. In the present study, we examined the effects of cilnidipine and amlodipine on the renal injury in spontaneously hypertensive rat/ND mcr-cp (SHR/ND) and their underlying mechanism.Methods and results-SHR/ND were treated with vehicle (n = 10), cilnidipine [33 mg/kg per day, orally (p.o.); n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 44 publications
4
50
0
Order By: Relevance
“…Also, albumin overload was shown to increase intracellular calcium ion concentration ([Ca 2ϩ ] i ) in podocytes both via the Ca 2ϩ influx and the release of the intracellular Ca 2ϩ stores (8). A number of cation channels have been identified to cause Ca 2ϩ influx in podocytes (16,35,58,68). Among them, TRPC6 has been attracting most attention.…”
Section: Discussionmentioning
confidence: 99%
“…Also, albumin overload was shown to increase intracellular calcium ion concentration ([Ca 2ϩ ] i ) in podocytes both via the Ca 2ϩ influx and the release of the intracellular Ca 2ϩ stores (8). A number of cation channels have been identified to cause Ca 2ϩ influx in podocytes (16,35,58,68). Among them, TRPC6 has been attracting most attention.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, even previous studies reported better renoprotective effects of cilnidipine than amlodipine. 26,27 Cilnidipine was shown to prevent the increase in renal angiotensin II content in spontaneously hypertensive rat/ND mcr-cp (an obese spontaneously hypertensive model). 26 In addition, it reduced renal ACE activity and renal aldosterone content in uninephrectomized deoxycorticosterone-salt hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Cilnidipine was shown to prevent the increase in renal angiotensin II content in spontaneously hypertensive rat/ND mcr-cp (an obese spontaneously hypertensive model). 26 In addition, it reduced renal ACE activity and renal aldosterone content in uninephrectomized deoxycorticosterone-salt hypertensive rats. 27 However, in the present study, the activity of renal RAS system in hypertensive patients was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…For cilnidipine the result could be explained by the less activation of RAS. A recent report suggests that cilnidipine suppressed the development of proteinuria greater than amlodipine possibly through inhibiting N-type calcium channel-dependent podocyte injury in SHR/ND [36]. For efonidipine, the result might be explained by suppression effect on transcription of aldosterone synthase (CYP11B2) [37].…”
Section: Discussionmentioning
confidence: 99%